2021
DOI: 10.46542/pe.2020.202.297301
|View full text |Cite
|
Sign up to set email alerts
|

A study on the effectiveness of online teaching in pharmacy education from teacher and student perspectives during the COVID-19 pandemic

Abstract: Introduction: Technology is a proven teaching aid, and online teaching has facilitated teaching across borders; however although technology has been proved to be an effective teaching aid, it cannot replace a teacher. There are many reports that discuss the constraints of only using online classes, as a result the use of both online and face to face classes has been advocated. The COVID-19 pandemic, however, has forced teachers and lecturers to rely solely on online classes. Methods: The authors conducted a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 19 publications
(11 reference statements)
1
6
0
Order By: Relevance
“…12 Panda et al in his study reported that internet speed and technical issues were major barriers, whereas flexibility, availability of content for revision and fewer distractions were the positive features of online learning. 13 The current study highlighted that more than three-fourth (76.8%) of the nursing students had poor online learning self-efficacy scores in all the domains. Additionally, scores were also poor for majority of the participants in learning, technical and time management aspects.…”
Section: Discussionmentioning
confidence: 65%
“…12 Panda et al in his study reported that internet speed and technical issues were major barriers, whereas flexibility, availability of content for revision and fewer distractions were the positive features of online learning. 13 The current study highlighted that more than three-fourth (76.8%) of the nursing students had poor online learning self-efficacy scores in all the domains. Additionally, scores were also poor for majority of the participants in learning, technical and time management aspects.…”
Section: Discussionmentioning
confidence: 65%
“…Indonesian pharmacy teachers also opined that internet connectivity is the main obstacle in online teaching and learning [ 11 ]. The slow internet connectivity results in students’ disengagement during online teaching session [ 12 ]. Another report from Saudi Arabia also second the problems of technological, communication, students’ evaluation and health due to excess computer use [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hybrid approach is a better choice in their opinion. Saudi pharmacy teachers were also in favor of hybrid approach especially in case of pharmacy education and suggested online teaching during any pandemic situation [ 12 ]. Another researcher also favors hybrid approach [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although it was necessary but it had largely disrupted the education system. Studies report that both students and teachers feel that elearning cannot replace the traditional teaching style [12].…”
Section: Introductionmentioning
confidence: 99%